Dampak Misi Gereja Katolik terhadap Hilangnya Tradisi Kayau di Kalbar: Analisis Budaya Franz Boas - Fransesco Agnes Ranubaya; Alpinus Pan; Ignasius Ageng Prasetyo; Fransiskus Antonius Dimas Satyawardhana (Journal of Education, Humaniora and Social Sciences (JEHSS), 2024)
This article aims to examine the influence of the Catholic Church's mission on the disappearance of the ‘kayau’ tradition among the Dayak tribe in West Kalimantan. The problem is focussed on how the teachings and activities of the Catholic Church have influenced cultural change in the Dayak society, particularly in the context of reducing or eliminating violent practices such as ‘kayau’ or head hunting. In order to approach this problem, theoretical reference used is Franz Boas' theory of cultural change, which emphasises the influence of external factors and cultural interactions. emphasises the influence of external factors and cultural interaction. Data were collected through desk research, including literature from scientific journals, books and other sources, and analysed qualitatively, and other sources, and were analysed qualitatively. This research concludes that the mission of the Catholic Church in West Kalimantan succeeded in changing Dayak Dayak culture, especially abolishing the kayau tradition, by promoting peace, love, and respect for life. Through inculturation and social services, the Church replaced the tradition of violence with a peaceful and inclusive approach. and inclusive approach. According to Franz Boas' theory, these changes demonstrate the dynamic interaction between religious teachings and local culture. between religious teachings and local culture.